Larangan Perempuan Berbicara dalam Jemaat: Kajian Hermeneutik terhadap 1 Korintus 14:34–35 dalam Konteks Sosial-Teologis - Molle, Jhonderic (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2025)
This study aims to interpret 1 Corinthians 14:34–35 through a historical-critical hermeneutical approach in order to understand the meaning of the prohibition against women speaking in the congregation. By examining the social, cultural, and argumentative context of Paul’s writing, this study evaluates whether the prohibition is theological-normative or pastoral-contextual. The analysis shows that the text emerged from a specific situation in the Corinthian church, which was facing liturgical disorder. Therefore, the prohibition should not be understood as a universal command, but rather as a pastoral response to a particular situation. This study proceeds with a constructive theological approach to formulate practical implications for today's church, especially in encouraging equal participation of women in ministry. The theology developed from this text should not restrict women’s roles but instead affirm their active and equal involvement in the life of the congregation.